2020
DOI: 10.1371/journal.pone.0233500
|View full text |Cite
|
Sign up to set email alerts
|

The perceived impact of isoniazid resistance on outcome of first-line rifampicin-throughout regimens is largely due to missed rifampicin resistance

Abstract: BackgroundMeta-analyses on impact of isoniazid-resistant tuberculosis informed the World Health Organization recommendation of a levofloxacin-strengthened rifampicin-based regimen.We estimated the effect of initial rifampicin resistance (Rr) and/or isoniazid resistance (Hr) on treatment failure or relapse. We also determined the frequency of missed initial and acquired Rr to estimate the impact of true Hr. MethodsRetrospective analysis of 7291 treatment episodes with known initial isoniazid and rifampicin stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…Data from Bangladesh, used for calculation of RR probabilities after treatment and retreatment failure, are not necessarily applicable to Mozambique. 6 The probability of RR-TB in HIV-positive retreatment cases estimated as alternative starting point (24%) approached the estimate of the pretest probability of RR-TB in first treatment failure cases (20%) because of initial RR-TB in HIV-positive patients, but was lower than the estimated 43% for a HIVpositive case with treatment failure, with a large UI. This could be explained by the fact that patients with a TB history include patients with treatment failure and those with reinfection.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Data from Bangladesh, used for calculation of RR probabilities after treatment and retreatment failure, are not necessarily applicable to Mozambique. 6 The probability of RR-TB in HIV-positive retreatment cases estimated as alternative starting point (24%) approached the estimate of the pretest probability of RR-TB in first treatment failure cases (20%) because of initial RR-TB in HIV-positive patients, but was lower than the estimated 43% for a HIVpositive case with treatment failure, with a large UI. This could be explained by the fact that patients with a TB history include patients with treatment failure and those with reinfection.…”
Section: Discussionmentioning
confidence: 78%
“…When diagnosis of RR-TB depends on such tests, RR-TB patients with mutations outside of the RRDR may be repeatedly treated with first-line regimens, mostly without success. 4,6 The probability of disease required to treat a patient, or the therapeutic threshold, with equipoise between treating and not treating, 7 has not yet been estimated for RR-TB. 8 Current guidelines recommend all TB patients should be tested for RR.…”
Section: Introductionmentioning
confidence: 99%
“…(25) Some studies suggested that rifampicin phenotypicmolecular discordance may be associated with poor outcomes among patients treated with recommended firstline regimen. (27,28) We found two novel mutations in our samples. One mutation in rrs1402 ATG/AAG was suggestive for aminoglycoside resistance, but it has never been reported elsewhere.…”
Section: Resultsmentioning
confidence: 57%
“…Recently conducted systematic review and meta-analysis, reported significant higher failure rate among INH resistant compared to susceptible TB patients when treated with standard first-line drugs regimens [ 13 ]. Limitations of currently available pDST and gDST in detecting RMP resistance are well recognized [ 25 27 ]. Selection of either one of the two DST method for routine practice is likely to result in important diagnostic and clinical implications.…”
Section: Discussionmentioning
confidence: 99%
“…In our study population, without genotypic DST, 10.1% (411/4078) of the MDR would have been reported as RsHr-TB and treatment in these instances with standard first line treatment regimen would likely have resulted in suboptimal treatment outcomes. In a recently published study, a non-negligible extent of misclassifying MDR-TB as INH-resistant TB is demonstrated and impact of treating patients with missed RMP resistance for RsHr-TB with WHO recommended FQ containing regimen is strongly argued [27]. In another study from South Africa 15% of INH resistant isolates initially tested negative for RMP resistance by all three WHO-endorsed commercial tests were reclassified as MDR on identification of resistance conferring mutation (rpoB Ile491phe) using deep sequencing [28].…”
Section: Plos Onementioning
confidence: 99%